Abundance of Ticks (Acari: Ixodidae) and Presence of Rickettsia and Anaplasma in Ticks Infesting Domestic Animals From Northern India. Issue 3 (20th January 2021) - Misra, Brij Ranjan; Kumar, Niraj; Kant, Rajni; Deval, Hirawati; Singh, Rajeev; Pandey, Ashok Kumar; Behera, Sthita Pragnya; Bondre, Vijay P
Abstract: Rickettsia and Anaplasma are bacteria that can be transmitted by hematophagous arthropods such as ticks infesting animals in close proximity to humans. The main objective of the present study was to investigate abundance of common tick species infesting domestic animals and presence of Rickettsia and Anaplasma in tick populations. Adult ticks were collected from domestic animals in rural areas and screened by molecular detection of bacterial DNA for these two genera of bacteria. A total of 1, 778 adult ixodid tick specimens were collected from 200 cattle, 200 buffaloes, 200 goats, and 40 dogs. The collection consisted of four species of ixodid ticks, Rhipicephalus ( Boophilus) microplus (Canestrini) (83.8%), Hyalomma kumari (Sharif) (7.1%), Rhipicephalus sanguineus (Latreille) (6.4%), and Dermacentor auratus (Supino) (2.7%) infesting the domestic animals. The prevalence of all the collected tick species was highest in the month of October . Anaplasma spp. was the most frequently identified bacteria (3.3%) in tested ticks. Of 17 positive tick pools for Anaplasma spp., 14 pools were from ticks infesting cattle, 2 pools of ticks collected from buffalo, and the remaining pool were ticks infesting a goat at the time of collection. Although 1.6% tick pools of R. microplus collected from cattle tested positive for Rickettsia spp., present investigation provides evidence of the most prevalent ixodid ticks infesting domestic animals and the presence of obligate intracellular bacteria, Rickettsia and Anaplasma, in these ticks collected in the Gorakhpur division of Northern India.